Implementation of Transformational Education Management Model at SMKN 1 Pantai Cermin: Challenges and Opportunities - Haloho, Ronald Hervin; Lubis, Wildansyah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In facing the dynamics of the times, the implementation of the Transformational Education Management Model at SMKN 1 Pantai Cermin requires a deep understanding of critical aspects involving educational actors. One solution that attracts attention is the implementation of the Transformational Education Management Model at the level of SMKN 1 Pantai Cermin. This model emphasizes not only on the academic aspect, but also on the development of the student's personality, social skills, and intrinsic motivation necessary for success in life. The purpose of this study is to know implementation of transformational education management model at SMKN 1 Pantai Cermin: challenges and opportunities. This research method uses Descriptive method Analysis with a type of qualitative research, which is a type of research that describes phenomena or facts on the object under study to take the essence of each phenomenon. The results of this study show that The implementation of the Transformational Education Management Model in Senior High School (SMKN 1 Pantai Cermin) has produced promising results, along with an average score of 7.4. Despite the positive achievements, the evaluation shows several areas that need further attention. Increased parental involvement, in particular, is a top priority to ensure the full support of all stakeholders in a student's educational journey. Success in stimulating teacher creativity and student learning interest is a positive point, giving an indication that this model is effective in creating a dynamic learning environment.